New Students Recruitment System and Factors Influencing Their Choice: A Study at a State University in West Sumatera - Suswati Hendriani; Kasmuri Kasmuri; Reni Susanti; Fitra Kasma Putra (IAIN Batusangkar, 2022)
Recruiting new students quantitatively and qualitatively adequate to be able to get advancement and to exist is a routine agenda of a university. Thus, new student recruitment activity should be well done and well planned so that optimum results can be reached. Ideally, new student recruitment system is done by a specific permanent body whose task is to think about the best ways to get new prospective students. This can be realized when many parties are involved to get worthy suggestions. Of course each university has different methods, Therefore, this article is aimed at completing knowledge gap on new student recruitment system and factors influencing their choice of university. Through this research, new student recruitment system at IAIN Batusangkar was found out. The study used cross-sectional design. The population of the research was all the students of IAIN Batusangkar. The sample of the study was selected using cluster sampling technique in which 3.485 students were selected to be the reseach sample. The instrument used to collect the data of the research was a closed-ended questionnaire. The collected data was analyzed through Descriptive Statistics. The results of the research showed that there was an increase of promotion effectiveness from ineffective level in 2016 (51.01%) to effective level (62.45%) in 2018. The success of the new recruitment system to recruit new students because it was carried out in various ways, ranging from the use of brochures, scholarships, to promoting the accreditation value of the study program and institution. The most dominant factors in influencing student decision in choosing a university were parents and relatively affordable tuition.